The fishmeal revolution : the industrialization of the Humboldt Current ecosystem - Wintersteen, Kristin A., 1979- (University of California Press, 2021)
"Off the Pacific coast of South America, nutrients mingle with cool waters rising from the ocean's depths, creating one of the world's most productive marine ecosystems: the Humboldt Current. Its teeming populations of fish became a key ingredient in animal feed, as fishmeal from this region fueled the revolution in chicken, hog, and fish farming that swept the United States and Northern Europe after World War II. The Fishmeal Revolution explores industrialization along the Peru-Chile coast as fishmeal producers pulverized and exported unprecedented volumes of marine proteins in order to satisfy the growing taste for meat among affluent consumers in the global North. A relentless drive to maximize profits from the sea occurred at the same time that Peru and Chile grappled with the challenge, and potentially devastating impact, of environmental uncertainty. In her exciting new book, Kristin A. Wintersteen offers an important history and critique of the science and policy that shaped the global food industry"--